Modern Approaches to Enterovirus-Based Oncolytic Immune Virotherapy of Malignant Diseases - E. R. Nemtsova; E. A. Plotnikova (Фармация и фармакология (Пятигорск), 2025)
The aim. The review presents the analysis of publications on modern approaches to oncolytic viral immunotherapy of malignant diseases which is predominantly based on usage of enteroviruses.Materials and methods. Electronic data bases — PubMed, Scopus, Web of Science, Google Scholar, eLibrary, and other accessible datasets were used for gathering and analyzing appropriate publications for the following keywords: oncolytic virotherapy, oncolytic viruses, enteroviruses, poliovirus, coxsackievirus, echovirus, preclinical and clinical trials. The research included the time interval from 1990 till 2024.Results. The data present the properties of wild type and gen modified viruses — the supposed basis for development of the drugs, as well as their action mechanisms. The described mechanisms include direct cytolysis caused by the intracellular reproduction of the virus, activation of antitumor immunity of the host body (viral recipient) due to presentation of the tumor-associated antigens from the damaged cells to dendritic cells for their further maturation, presentation of these antigens to T-lymphocytes and activation of cytotoxic lymphocytes, modulation of tumor microenvironment due to immunostimulation,  and transition of “cold” tumor and its environment into “hot” state. It has been noticed that the most pronounced therapeutic efficacy is observed in immunosensitive tumors. This observation correlates with the action mechanism of the oncolytic viruses.  Clinical trials of viral drugs still have not led to superior results in therapeutic efficacy but they have demonstrated the synergistic efficacy with other methods of conservative therapy. According to the results of preclinical and clinical trials, enteroviruses demonstrate a favorable toxic profile. Factors which reduce the efficacy of virotherapy were evaluated. They include non-targeted and non-specific absorption of viruses by tumor cells, weak endocytosis and reproduction followed by distribution in the body, preexisting immunity against the concrete viruses and induction of antiviral antibody expression during viral therapy, and lack of sensitivity of the tumor and its microenvironment to the virus.Conclusion. Enterovirus-based oncolytic therapy is a promising therapeutic option but its efficacy needs to be enhanced using mechanisms of its therapeutic impact.